EXPLORING THE CHANGES TOWARDS ACCRUAL ACCOUNTING IN INDONESIAN LOCAL GOVERNMENTS - Mutoharoh Mutoharoh (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2018)
recently has been discussed much by scholars. Accounting reform as one of the primary agendas within this issue was limited to being addressed in terms of the actual process embedded in the internal organization routine. By utilizing a comparative case study of three departments in the regency level of the Indonesian government, this research aims to explore the process of the introduction of accrual accounting in Indonesia which is facing the sedimented process. The research engages the archetype theory to examine the outcomes achieved by the cases here and a set variable of intra-organizational dynamics. The interviews were organized to obtain the perspective of people involved, combined with textual analysis to clarify the interviewees answer. Radical and incremental outcomes were found, yet consistent patterns in terms of commitment, interest, technical capabilities and managerial capabilities were only associated with radical change. The lack of human resources and the role of the leaders in persuading their staff of the value of reform needs to be reshaped to reach a better outcome.Keywords: NPM, Indonesia, accrual accounting, departments